2021
DOI: 10.3390/ijerph18073712
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Gait Speed and Falls in Community Dwelling Older Adults with and without Mild Cognitive Impairment

Abstract: (1) Background: Falls are common in older adults and result in injuries, loss of independence, and death. Slow gait is associated with falls in older adults, but few studies have assessed the association between gait speed and falls among those with mild cognitive impairment (MCI). (2) Methods: The association between gait speed and falls was assessed in 2705 older adults with and without MCI participating in the Ginkgo Evaluation of Memory Study. Gait speed was measured via a 15-foot walk test and fall histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…An attempt to investigate the relationship between gait and cognition not only provides a better understanding of function but also provides an assessment of safety during movement. Decreased ability to walk during a single-or cognitive dual-task has been reported to be a contributing factor to falls in older adults and individuals with cognitive decline [33,34]. Dual-task gait assessment, where individuals have to perform a secondary attentional challenging task while walking, was shown to be more challenging as the tasks interfere with each other and divide the cortical control resources of the brain [35].…”
Section: Introductionmentioning
confidence: 99%
“…An attempt to investigate the relationship between gait and cognition not only provides a better understanding of function but also provides an assessment of safety during movement. Decreased ability to walk during a single-or cognitive dual-task has been reported to be a contributing factor to falls in older adults and individuals with cognitive decline [33,34]. Dual-task gait assessment, where individuals have to perform a secondary attentional challenging task while walking, was shown to be more challenging as the tasks interfere with each other and divide the cortical control resources of the brain [35].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Bohannon and Glenney 32 summarized information on the minimal clinically important difference for changes in comfortable gait speed among patients with various pathologies, suggesting that alterations of 0.10–0.20 m/s might serve as minimal clinically important difference across multiple patient groups. Furthermore, Adam et al 33 concluded that a gait speed change of 0.10 m/s is generally accepted in clinical practice as an indicator of elevated fall risk among older adults, with a mean age of 78.5 years, regardless of their cognitive status. Based on the minimal clinically important difference values available from prior studies on different gait variables, our study's results indicate the presence of minimal clinically important differences in stance time between both groups at post-1 and post-2, in favor of the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, reports related to association between gait speed and cognitive subdomains are available on older adults with mild cognitive impairment (MCI) 26 or with high risk of falling. 27,28 Moreover, physical frailty subdomains can predict the development of social frailty, including gait performance and muscle strength. 29 Considering the above backgrounds, independent risk factors towards social frailty among older adults need to be investigated in the future, as well as monitoring physical and cognitive functions.…”
Section: Discussionmentioning
confidence: 99%